Initial Study on Milling in an Ultrasonically Excited Metalworking Fluid Bath - Gross, Daniel; Eichinger, Miriam; Selzam, Jan Harald; Hanenkamp, Nico (Lecture Notes in Mechanical Engineering, 2025)
Energy and resource efficiency are seen as key drivers of the industrial transformation towards a low carbon economy. In particular, machine tools, which are essential to value creation, have a significant share of industrial greenhouse gas emissions due to their high-energy consumption. The energy demand for the provision and supply of metalworking fluids (MWF) alone can account for up to 25% of the total energy demand. The aim of this study is to investigate and fundamentally design an alternative cooling lubricant concept. This concept does not require continuous pumping of the coolant supply. Instead, the milling operation takes place in an immersion bath filled with metalworking fluid. An additional ultrasonic (US) actuator causes the coolant to vibrate, allowing the coolant to penetrate deeper into the cutting zone. The machining tests include a comparison of classic flood cooling, immersion bath milling and immersion bath milling with US stimulation. To compare the processes, the flank wear, the workpiece surface roughness and the bending moments due to the cutting forces were analyzed. The energy assessment allows a final evaluation of the processes.
CRIS-Team Scopus Importer:2025-02-28
Keywords: energy efficiency; immersion bath; Milling; ultrasonic